2000
DOI: 10.5459/bnzsee.33.1.30-47
|View full text |Cite
|
Sign up to set email alerts
|

Analytical modelling of infilled frame structures

Abstract: The analytical modelling of infilled frames is a complex issue because these structures exhibit a highly non- linear inelastic behaviour resulting from the interaction of the masonry infill panel and the surrounding frame. This paper presents a general review of the different procedures used for the analysis of infilled frames, which can be grouped in local or micro-models and simplified or macro-models, depending on the degree of refinement used to represent the structure. The finite element formulation and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
110
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(114 citation statements)
references
References 27 publications
0
110
0
4
Order By: Relevance
“…For this reason, such structures are usually modeled by means of so-called macro-models, which consist of beam/column elements and diagonal struts representing the masonry infills. A comprehensive overview of variants of diagonal-strut models for infilled frames was performed by Crisafulli et al or, more recently, by Asteris et al [1,2]. The simplest model of an infilled frame consists of a frame model and compressive diagonal struts, which are connected to the frame through the beam-column joints.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, such structures are usually modeled by means of so-called macro-models, which consist of beam/column elements and diagonal struts representing the masonry infills. A comprehensive overview of variants of diagonal-strut models for infilled frames was performed by Crisafulli et al or, more recently, by Asteris et al [1,2]. The simplest model of an infilled frame consists of a frame model and compressive diagonal struts, which are connected to the frame through the beam-column joints.…”
Section: Introductionmentioning
confidence: 99%
“…This was proven, for example, in Smyrou et al (2011), comparing the results of a pseudo-dynamic test on a full-scale, four-storey, three-bay, RC frame with a numerical macro-model. Crisafulli et al (2000) demonstrated the same limitation by comparing the pushover results of single-, two-and three-struts models of an ideal one-bay, one-storey frame to a refined finite element model (Fig. 3).…”
Section: Infilled Frames Modelling Techniques: Literature Reviewmentioning
confidence: 84%
“…Fig. 3 Bending moment comparison for a one-bay one-storey frame using different models for the infill (modified after Crisafulli et al 2000) compression only (see Fig. 2f).…”
Section: Proposed Decoupling Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…ISSN: 2321-9653; IC Value: 45.98; SJ Impact Factor: 6.887 Volume 7 Issue IV, Apr 2019-Available at www.ijraset.comCrisafulli et al(2000) …”
mentioning
confidence: 99%